Overview at autonomous construction development tendencies - Karpenko, A. S. (ХНУРЕ, 2024)
In this article main areas of research on construction automation, as well as reasons for their studying, are defined.
Keywords: constructional automation; construction 4.0; constructional IoT; robotics